Caracterización de la intención emprendedora y su incidencia en la economía de las madres solteras de la Parroquia San Camilo, año 2022 - Balcazar Ubillu , Sara Mariuxi (2024)
The study carried out in the canton of Quevedo, parish of San Camilo, in 2022, aimed to characterize the entrepreneurial intention and its impact on the economy of single mothers. The study aims to know the entrepreneurial intention of single mothers and how it affects their economy, which generates satisfaction for them to have an entrepreneurship, this being an opportunity for single mothers to improve their economic situation and their quality of life. To do this, they need to receive support and training and be able to develop their ventures successfully. In this sense, this work was developed in the urban area of the canton of Quevedo parish of San Camilo. Because of this, the study population is made up of women from the urban area of the Quevedo canton where there is a number of women who do not have a job and require the impulse to become entrepreneurs. The research is qualitative, quantitative, field research, descriptive and analytical, methods such as analysis, deductive and inductive and historical logic were used, an interview guide and a questionnaire were developed to obtain data, to then be tabulated and analyzed. We can observe that based on the results, the single mothers of the parish of San Camilo have not been able to undertake due to lack of capital, lack of studies, training, fears such as fear of failure, even lack of support in the care of their children, this makes them stop at the moment of wanting to start a business.